Exposure to BDE-153 induces autophagy in HepG2 cells - Pereira, Lilian Cristina [UNESP]; Duarte, Filipe Valente; Varela, Ana Teresa Inácio Ferreira; Rolo, Anabela Pinto; Palmeira, Carlos Manuel Marques; Dorta, Daniel Junqueira (Elsevier, 2017)
Autophagy is a pro-survival process that occurs under stressful “life-threatening” conditions. This process clears the cells of damaged organelles, long-lived proteins, and/or misfolded proteins. Under stressful conditions, activation of the autophagic process leads to cell death and acts as a protective mechanism against xenobiotic, which is the most widely accepted mechanism in the literature. Exposure to flame retardants and other pollutants is associated with several diseases, during which cell death and mitochondrial damage takes place. Although a body of research has aimed to understand the toxicity mechanism of flame retardants better, risk evaluation and the consequences of exposure to these toxicants have been poorly described. In this work, we have found that the BDE-153 congener (representant of flame retardants) induces autophagy after 24 and 48 h (0.1–25 μM). The autophagic process is associated with accumulation of lysosomes, and process triggering is evident from the levels of autophagy-related proteins such as p62 and LC3. Mitophagy (an autophagic process that specifically involves damaged mitochondria) may be involved, as judged from the decreased amount of mitochondrial DNA. Taken together, our results point out that induction of autophagy upon cell should contribute to better understanding of the consequences of human exposure to this class of environmental contaminants.
Keywords: Autophagy induction; BDE-153, flame retardants; Mitophagy